Contribuição ao estudo termodinâmico das soluções de ácido acetilsalicílico - Maia, Gustavo Dias (Universidade Federal de São Carlos, 2007)
As one of the most regularly traded-in medicines in the world, the acetylsalicylic acid has been scarcely researched when in solution. This study is aimed at determining the thermodynamic equilibrium parameters for thermodynamic models such as Margules, Van Laar, Wilson, NRTL, UNIFAC, Regular Solution Theory, and Nývlt for acetylsalicylic acid solutions in ethanol, acetone, propylene glycol, and isopropyl alcohol, in addition to comparing their solubility values with the expected from an ideal solution and with some solutions of solvent diluted in water to evaluate the effect of the water addition in the solvent Moreover, the study of the solubility parameters became to compose the sphere of solubility of the acetylsalicylic acid with some solvents adds the used ones to determine the solubility curves. We also do the study of the decomposition of the acetylsalicylic acid became during the procedure for the determination of its curves of solubility. Through djustments it is possible to conclude that the Nývlt model presented the best correlation rate (0,999) for the adjustment of its parameters. Moreover, it was the best model to represent the experimental data with an average percent deviation of 1%. The NRTL model also presented good adjustment rates when compared with other experimental data. It is an interesting tool to predict the activity coefficient of the acetylsalicylic acid solutions for all the solvents under study. The UNIFAC model presented an inadequate prediction of activity coefficient values with average percent deviations of up to 70%. The solubility sphere was determined in satisfactory way, once the solubility parameters of acetylsalicylic acid is in compliance with the solvents parameters. The assays for the determination of the decomposition of the acetylsalicylic acid had demonstrated that it does not have significant degradation of acetylsalicylic acid throughout the experiments for ethanol, propylene glycol and isopropyl alcohol.
Keywords: Termodinâmica; Solubilidade; Coeficiente de atividade; Aspirina; ENGENHARIAS::ENGENHARIA QUIMICA